Asymptotic stability of fractional difference equations with bounded time delays - Wang, Mei; Jia, Baoguo; Du, Feifei; Liu, Xiang (Fractional calculus & applied analysis, 2020)
In this paper, an integral inequality and the fractional Halanay inequalities with bounded time delays in fractional difference are investigated. By these inequalities, the asymptotical stability conditions of Caputo and Riemann-Liouville fractional difference equation with bounded time delays are obtained. Several examples are presented to illustrate the results.